Study on the effect of different salinity level to paddy growth performance: a research / Mohamad Fitri Alias - Alias, Mohamad Fitri (Faculty of Plantation and Agrotechnology, 2018)
The study of effect different salinity on paddy growth performance an experiment was conducted in greenhouse or rain shelter UiTM Jasin in Complete Randomized Design (CRD) based on 5 replications. The variety of rice use is MR219 and the different level of salinity were dilute with fresh water in 3 level rate which is 20 ppt / kg of salinity, 35 ppt / kg of salinity and 50 ppt / kg of salinity. Inorganic fertilizer NPK with recommended rate also was used in this experiment. The rice without salinity level was served as control. Dilute solutions of different level of salinity (ppt) had a beneficial effect on paddy growth at all measured parameters such as the height of plant, the length of leaf blade and the number of tillers. The height and its components were showed a significant different between the treatment. The maximum mean of plant growth was noted in plant that treated with 20 ppt / kg of salinity level that excellent of growth performance of paddy with the highest of mean value of height (73.06 cm), highest mean of leaf blade length (40.06 cm) and the highest mean number of tiller (18.2). So, from this study the higher level of salinity water give bad impact and poor performance for paddy growth.